Health care professionals’ experiences with goal setting during initial rehabilitation after newly acquired spinal cord injury/ disorder – a qualitative focus group study - Lampart, Patricia; Schäppi, Livia; Langewitz, Wolf Axel; Rubinelli, Sara; Sigrist-Nix, Diana; Scheel-Sailer, Anke (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Goal setting (GS) is an important aspect of initial spinal cord injury/ disorder (SCI/D) rehabilitation. However, because expected outcomes are individual and often difficult to determine, GS is not straightforward. The aim of this study was to explore the health care professionals’ (HCP's) experiences with and perspectives on the goal-setting process (GSP) during initial SCI/D rehabilitation. Method: Five semi-structured focus groups (FG) (22 purposively sampled HCP, mostly in leadership positions, six different professions). The FG were transcribed verbatim. We analyzed the transcripts for qualitative content analysis following Braun and Clarke (2013). Results: HCP described GS-influencing aspects at the macro, meso and micro levels. At the macro level, participants spoke about restrictions imposed by health insurers or difficulties in planning the post-inpatient setting. Regarding the meso level, HCP spoke of institutional structures and culture that facilitated the GSP. At the micro level, knowledge of the diagnosis, expected outcomes, and individual patient characteristics were mentioned as important to the rehabilitation process. It was important for HCP to be patient and empathetic, to endure negative emotions, to accept that patients need time to adjust to their new situation, and to ensure that they do not lose hope. Open communication and interprofessional collaboration helped overcome barriers in the GSP. Discussion: This paper shows the complex relationship between external (e.g., health insurers), emotional, and communication aspects. It calls for a comprehensive approach to optimizing the GSP, so that patients’ experiences can be fully considered as a basis to identify the most appropriate care pathway.